Ethical perspective of students in Global Learning Environment - Muhammad, AbdulHafeez; Ahmad, Farooq; Shah, Asadullah (2013)
Recent developments in the fields Information & Communication Technologies (ICTs) have created unprecedented changes in the way we deal and communicate. The learning environment, which plays a major role in the academic success and character development of students, has also been affected. Learning processes have evolved throughout the history of mankind. Electronic Learning (e-Learning) is the next evolutionary mode of learning of academic institutions to educate students in a Global Learning Environment (GLE). GLE has provided a lot of opportunities for academic institutions, but it has also extended the opportunities for students to behave unethically in their online academic activities which affect their character. So it’s challenging for academic institutions to develop the character of students by controlling their unethical behavior in GLE. The work is to investigate the factors behind this challenge and then propose a model using ICTs, which will help to develop character of students along with domain knowledge.